2019
DOI: 10.1142/s1464333219500170
|View full text |Cite
|
Sign up to set email alerts
|

Conflicting Demands on the Natural Resources in Northern Sweden: A Participatory Scenario Development Study

Abstract: Globalisation strongly influences social, environmental and economic resources, especially in those territories characterised by a historical dependency on a single industry, as in the case of mining. Our study aimed to envision possible future development paths for the mining city of Gällivare, in Northern Sweden, using a participatory approach. Four different transformative narratives were developed depicting a wide range of choices along an ideal anthropocentric-wild gradient. Through applying complementary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…This is consistent with previous studies that advocated for allocating large, connected areas with reduced human intervention to promote the recovery of biodiversity and functional ecosystems, for example, as offered by abandoned lands (Pereira and Navarro 2015, Svenning 2020). We found that the creation of green corridors for enhancing connectivity (Van Berkel and Verburg 2012, Martinez‐Sastre et al 2017, Perez‐Soba et al 2018) and an increase of strictly protected areas for restoring trophic processes and natural dynamics (Haatanen et al 2014, Palomo et al 2017, Accastello et al 2019) were most cited in narratives creating space for nature. However, tradeoffs were often mentioned in scenarios that prioritized rewilding, such as reduction of perceived cultural value and conflicts over land use prioritization (Hanspach et al 2014, Palomo et al 2017, Accastello et al 2019, Vannier et al 2019).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This is consistent with previous studies that advocated for allocating large, connected areas with reduced human intervention to promote the recovery of biodiversity and functional ecosystems, for example, as offered by abandoned lands (Pereira and Navarro 2015, Svenning 2020). We found that the creation of green corridors for enhancing connectivity (Van Berkel and Verburg 2012, Martinez‐Sastre et al 2017, Perez‐Soba et al 2018) and an increase of strictly protected areas for restoring trophic processes and natural dynamics (Haatanen et al 2014, Palomo et al 2017, Accastello et al 2019) were most cited in narratives creating space for nature. However, tradeoffs were often mentioned in scenarios that prioritized rewilding, such as reduction of perceived cultural value and conflicts over land use prioritization (Hanspach et al 2014, Palomo et al 2017, Accastello et al 2019, Vannier et al 2019).…”
Section: Discussionmentioning
confidence: 97%
“…The prioritization of regulatory and material NCPs in the scenario narratives often responded to the need to secure the supply of these NCPs in an uncertain future of nature (Heikkinen et al 2010, Plieninger et al 2013, Rosenberg et al 2014, Accastello et al 2019. For example, in the Gällivare area (Sweden) a town which is going through a sectorial transformation from mining towards alternative economic activities, stakeholders were confronted with scenarios that explored futures in which nature conservation is prioritized versus scenarios where wood extraction or tourism takes place.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our case study, the aim of the PSP was to identify an ideal, yet plausible, future for the Saamaka and the external stakeholders as a starting point for working toward reconciliation of competing interests in the landscape. PSP can be used as a strategic tool to bring actors together to envision possible future pathways, especially in cases where natural resources or land-use conflicts exist (Patel et al 2007;Accastello et al 2019). The spatially explicit iterative approach was adapted from (McKenzie et al 2012;Addison and Ibrahim 2013) and based on the InVEST Scenario Generator tool ( © Natural Capital Project).…”
Section: Participatory Scenario Planningmentioning
confidence: 99%
“…This study examined the value of education and R&D investment in determining the impact of fiscal spending on green economic development in E-7 economies by sing econometric estimation. Accastello et al ( 2019 ), Molla et al ( 2019 ), and Pinto et al ( 2019 ) attempted to discover the composition effect and the technique effect. In contrast, the geographical variability in these cities may offer us sufficient data variability to accomplish the identification technique.…”
Section: Introductionmentioning
confidence: 99%